The Academic Community Perception About Implementation of UI GreenMetric-Waste Management Criteria at President University - Kezia Kusumaningtyas; Ramadhani Fithratullah; Clara Meluk (President University, 2019)
Universitas Indonesia is the initiator of a UI GreenMetric World University international ranking system, which is a ranking system that aims to bring together universities that share the same goals in terms of sustainability. At present President University has participated in the ranking system. To find out the perceptions of the academic community on the implementation of the ranking system at President University, one of the criteria that is examined is waste management as one of the parameters of the GreenMetric UI. To get data, the method of direct observation is done to get the desired data by making a questionnaire in the form of a google form filled in by students and interview staff and operators at President University. Based on the results of data processing, it can be seen that the academic community at President University campus in general does not fully understand the waste management system on campus. So that education needs to be done about the management system developed on the internal campus of President University.